Relationship between tumor markers CEA and CA15-3 and recurrence breast cancer - Rad Ghasabeh, Hadi; Keyhanian, Shahrbano (Archives of Advances in Biosciences, 2012)
The value of clinical use of tumor markers CEA and CA15-3 for early detection of recurrent breast cancer still is a controversial. This study was investigated relationship between tumor markers CEA and CA15-3 and recurrence breast cancer. Data regarding 147 women who had breast cancer were entered into the study. Patients were reviewed for 120 months after treatment. Maximum time for relapse was considered a 6 months. Results were showed recurrence cancer in 20% of diagnosed patients. All of them in diagnosis time had a higher of normal tumor markers (CA<3, CA15-3<30).These observations indicated that CA15-3 is a sensitive tumor marker for diagnosis especially for recurrent breast cancer.